1st International Postgraduate Conference on Mechanical Engineering (IPCME2018). (January 2019) - Unknown
Abstract : Preface The 1 st IPCME2018 The 1 st International Postgraduate Conference on Mechanical Engineering (IPCME2018) is the first conference organized by Faculty of Mechanical Engineering, Universiti Malaysia Pahang, Pekan campus that focus on participation of postgraduate student across the world. These proceeding contains the selected scientific manuscripts submitted to the conference. It is with great pleasure to welcome you to the "International Postgraduate Conference on Mechanical Engineering IPCME2018" that is held at Universiti Malaysia Pahang, Malaysia. The call for papers attracted submissions of over more than one hundred abstracts from both local and international universities. The scientific papers published in these proceeding have been revised and approved by the technical committee of the 1 st IPCME2018. All of the papers exhibit clear, concise, and precise expositions that appeal to a broad international readership interested in mechanical engineering. The topics of the Conference were: (1) Combustion; (2) Structural integrity and vibration; (3) Human and biomechanical; (4) Manufacturing system and process; (5) Energy and fuels; (6) Computational analysis and advanced materials; and (7) Thermal and fluid engineering. The reports present original ideas or results of general significant supported by clear reasoning and compelling evidence, and employ methods, theories and practices relevant to the research. The authors state clearly the questions and the significance of their research to theory and practice, describe how the research contributes to new knowledge, and provide tables and figures that meaningfully add to the narrative. In this edition of IPCME2018 representatives coming from academia, industry, governmental and private sectors. The plenary and invited speakers present, discuss, promote, and disseminate research in all fields of mechanical engineering in a constructive manner. Numerous social events that provide opportunities for the participants to renew old contacts and establish new ones were scheduled to accompany and follow the scientific activities. We want to thank the Organizing Committee, the University and Sponsors supporting the conference and everyone who contributed along the conference and publication of these proceeding. Professor Dr. Rizalman Mamat The Chairman of IPCME2018